Media relations after the introduction of social media - Mesila, Helin (2010)
In the light of the popularity of social media on one hand, and the contradictive relationships between journalists and public relations practitioners on the other hand, the thesis studies media relations after the introduction of social media. The study focuses on media relations in Estonian public relations scenery.